Paisanos A Folklore Miscellany - Abernethy, Francis Edward; Open Access Publishing in European Networks; Project Muse. (Texas A & M University Press [distributor], 1998)
Annotation The paisano, or roadrunner, is the emblem of the Texas Folklore Society chosen by the membership at the meeting held April 22, 1932, presided over by Jovita Gonzalez. This volume is liberally sprinkled with pictures of that fine bird, and it is written by paisanos, fellow countrymen in the realm of folklore. From the paisano's cactus corral by J. Frank Dobie to John Neal Phillips' exploration of the Anasazi; from Bill Brett's planting by the moon to the names of newspapers by C. Richard King; from Lawrence Clayton's fact and fiction in Lomax outlaw songs to home and farm remedies and charms in a German manuscript by Christine Boot; from a look at Sunday cock fights by F.E. Abernethy to the pet rock in American folklore by Olivia Murray Nichols, this miscellany shows the diversity of Texas folklore.
Description based on print version record.
Keywords: Social Science -- Folklore & Mythology; Folklore; Electronic book; Electronic books